Long Time Coming. Short Writings from Zimbabwe : Short Writings from Zimbabwe - Morris, Jane, 1953- (Book collections on Project MUSE., 2008)
Long Time Coming brings together short stories and poems from thirty-three writers that provide snapshots of this turbulent period in Zimbabwe's history. Snapshots of living in a country where basic services have crumbled: where shops have no food, taps no water, banks no money, hospitals no drugs, bars no beer. Snapshots of characters surviving against seemingly insurmountable odds. Horrific snapshots of the abuse of power, of violence and oppression, of the destruction of dreams. But this is Zimbabwe and there are lighter moments and moments of hope: in some of life's simple pleasures, in th.